Transcription initiation site of rat ribosomal DNA. - Rothblum, L I (1982)
The sequence of 1,100 nucleotides surrounding the transcription initiation site of a cloned rat ribosomal RNA gene (rDNA) has been determined. The location of the 5' terminus of 45S pre-rRNA was determined by S1 nuclease mapping, reverse transcriptase elongation and confirmed by in vitro capping of 45S rRNA and in vitro transcription. Two different plasmid subclones, from two separate genomic clones of rat rDNA, contained the identical sequence surrounding the transcription initiation site: -10GGAGATATAT 1GCTGACACGC TGTCCTTTTG+20. Relatively long, greater than 15 base pairs, regions of sequence homology were found when the sequences of the initiation regions of rat and mouse rDNA (Urano, Y., Kominami, R., Mishima, Y., and Muramatsu, M., Nucleic Acids Res. 8, 6043-6058, 1980) were compared. When both the rat and mouse sequences were compared to that of human rDNA (G. Wilson, personal communication) a sequence of 15 nucleotides immediately following the initiation sites were found to be preserved.